Synthesis, Spectroscopic Characterization (FT-IR, FT-Raman and NMR) and in vitro Anticancer Activity of (E)-5-Bromo-3-((4-chloro-3-(trifluoromethyl)phenyl)imino)indolin-2-one - Rekha, S.; Tamilselvan, S.; Nasibullah, Malik; Asif, Mohd; Manikandan, P.; Reeda, V.S. Jeba; Kaleeswaran, S. (Asian Journal of Chemistry, 2025)
This comprehensive study, combining theoretical insights with experimental validation, enhances the understanding of molecular structure, vibrational dynamics and electron delocalization through spectroscopic techniques. These methods were employed to analyze the synthesized hybrid oxindole Schiff base, specifically (E)-5-bromo-3-((4-chloro-(trifluoromethyl)phenyl)imino)indolin-2-one (5BTPIO) molecule, as well as its biological activities. Electron localization function (ELF), localized orbital locator (LOL) and reduced density gradient (RDG) investigations facilitated to classify the weakest interactions, bonding zones and electron energy density, respectively. The in vitro anticancer properties of the 5BTPIO molecule were also investigated. The in silico docking studies were executed to preliminarily assess the anticancer activity against 3G74, 4Z8Z and 7PGL proteins, revealing binding affinities of -6.08, -5.60 and -6.72 kcal/mol, respectively. DFT proved valuable in examining the stability of the molecular structure under optimal conditions, facilitating comparison studies that integrated both theoretical and experimental data.